From map to blueprint: the plant pan-genome unraveling genetic mysteries and powering precision breeding - Liu, Chong; Xu, Hang; Li, Zheng; Wang, Yukun; Zhang, Jiaxian; Qiao, Siwei; Zhang, Hao (Frontiers in Plant Science, 2025)
With the rapid advancement of sequencing technologies and bioinformatics, coupled with significant progress in sequencing efficiency and reduced costs, substantial breakthroughs have been achieved in plant functional genomics, evolutionary genetics, and molecular breeding. However, as research deepens, accumulating evidence demonstrates that reference genomes derived from a single individual fail to adequately represent the genetic diversity of entire species. This limitation has catalyzed the emergence of the pan-genome concept. Pan-genome research now stands at the forefront of plant genomics, serving as a pivotal area of focus. Its application in plant studies has unveiled extensive genetic variations, identified numerous novel genes, and significantly enhanced our understanding of genetic diversity within relevant species. This review comprehensively summarizes recent progress in plant pan-genome research, construction methodologies, current applications in plant science, and key achievements. Finally, we outline future research directions, aiming to provide a reference for theoretical and applied pan-genome studies while offering novel perspectives for deciphering the genetic basis of plant breeding, evolutionary domestication, and phenotypic diversity.